A Comprehensive Analysis Of Cable Bolt Anchorage Characteristics - D. D. Faulkner (Society for Mining, Metallurgy & Exploration, 2014)
Cable bolts anchored with traditional two component polyester resin cartridges have successfully supported difficult roof conditions in underground mines. Resin cartridges provide a cost-effective cable bolt anchoring system with consistent anchorage performance characteristics when properly installed. The most commonly used cable bolts in the U.S. mining industry are 270 ksi (1,862 MPa), 0.7 and 0.6 inch (18 and 15 mm), seven-strand smooth cable with resin mixing bulbs (also known as bird cages), and 40- and 30-ton nominal capacity, respectively. However, there are other types of cable bolt anchoring systems aside from bird cages. Recently, many questions have been raised regarding the anchorage characteristics of various types of cable bolts. Keystone Mining Services, LLC (KMS), the affiliated engineering company of Jennmar Corporation, conducted a variety of controlled tests developed to closely model actual underground installations. These tests compared the performance of three commonly used cable bolt varieties, including plain, bird caged and indented seven-strand cable. Details of the laboratory testing and comparative analysis of the results are provided.